Laboratory risk indicator for necrotizing fasciitis: an objective scoring system as a tool for early diagnosis of necrotizing fasciitis - Saad, Syed; P., Panchami; ., Gulamnabi (International Surgery Journal, 2021)
Background: Necrotizing soft tissue infections are often fatal, characterized by extensive necrosis of the subcutaneous tissues and fascia. The mortality of 30-40% reflects the inadequacy of early recognition of necrotizing soft tissue infections. This study emphasizes on the search for a tool that reliably and rapidly identifies patients with NF. An objective of current study was to validate the LRINEC score as a tool for early distinguishing of necrotizing fasciitis from other soft tissue infections. Methods: Prospective clinical study analysis of outcome of sixty of patients with soft tissue infections were evaluated based on LRINEC. Based on their LRINEC score, the patients were categorized as low, intermediate and high risk for the onset of necrotizing fasciitis. Results: A total of 60 patients with soft tissue infections were prospectively evaluated and categorized on the basis of LRINEC score 45 patients in low risk category, 7 in Intermediate risk and 8 patients in high risk group. In terms of outcome, all cases (including positive tissue diagnosis cases) in low risk and intermediate risk groups and 2 cases in high risk group were improved with surgical debridement/fasciotomy. The cutoff of LRINEC ≥6 has better sensitivity and specificity in identifying the risk of the patient. Conclusions: LRINEC scoring system has a better positive predictive value in identifying the onset and risk strategizing of necrotizing fasciitis.